Pengaruh Storytelling terhadap Perilaku Cuci Tangan Menggunakan Sabun dengan Benar pada Anak di TK AL-QODIRI Jember - Ayu Puteri Nur Perdani (Jurnal MID-Z (MIDWIFERI ZIGOT), 2018)
Hand washing nith soup is one of disease prevention efforis This is done because the hands are often the agents that carry germs and cause pathogens to move from one person to another Many diarrheal diseases in children caused by the behavior of children never wash hands before eating, it is due to lack of education to children In general, all children enjoy listening to the storytelling of both toddlers, elementary school age, and those who are teenagers Storytelling is an appropriate method to provide an education to children so that researchers are interested in researching “Effect of Storytelling on Handwashing Behavior Using Soap Properly In Children at TK Al-Qodiri".This study used a quasi-experimental design form. Based on the result of the research in TK Al-Qodiri Jember from 27 respondents of experimental group studied, the data obtained before the theories of 20 students (74.?%) less good. Then after given storytelling happened increase of behavior of hand washing using soap true number of 23 students (852%) Analysis of research results using man whitney lest significance value p   '' 0.000 ? = 0.05 results obtained by storytelling with handwashing behavior.